Changes in bottlenose dolphin whistle parameters related to vessel presence, surface behaviour and group composition. (July 2016) - Heiler, J.; Elwen, S.H.; Kriesell, H.J.; Gridley, T.
Abstract : Cetacean watching from tour boats has increased in recent years and has been promoted as an ethically viable alternative to cetacean viewing in captive facilities or directed take. However, short- and long-term impacts of this industry on the behaviour and energetic expenditure of cetaceans have been documented. Although multiple studies have investigated the acoustic response of dolphins to marine tourism, there are several covariates that could also explain some of these results and should be considered simultaneously. Here, we investigated whether common bottlenose dolphins, Tursiops truncatus, inhabiting Walvis Bay, Namibia vary their whistle parameters in relation to boat presence, surface behaviour and/or group composition. We detected an upward shift of up to 1.99 kHz in several whistle frequency parameters when dolphins were in the presence of one or more tour boats and the research vessel. No changes were demonstrated in the frequency range, number of inflection points or duration of whistles. A similar, although less pronounced difference was observed in response to engine noise generated by the research vessel when idling, suggesting that noise alone plays an important role in driving this shift in whistle frequency. Additionally, a strong effect of surface behaviour was observed, with the greatest difference in whistle parameters detected between resting and other behavioural states that are associated with higher degrees of emotional arousal. Group composition also contributed to the variation observed, with the impact of boats dependent on whether calves were present or not. Overall these results demonstrate high natural variation in the frequency parameters of whistles utilized by dolphins over varying behavioural states and group composition. Anthropogenic impact in the form of marine tour boats can influence the vocalization parameters of dolphins and such changes could have a long-term impact if they reduce the communication range of whistles or increase energy expenditure. Highlights: Investigation of whale watching impact on acoustic behaviour of bottlenose dolphins. Dolphins shift whistles to higher frequency as short-term response to tour boat/s. The research vessel had less impact on whistle acoustic parameters. Important covariates for results are emotional arousal and group composition. Monitoring necessary to minimize long-term effects.